Numerical analysis of the incineration of polychlorinated biphenyl wastes in rotary kilns. Issue 1 (March 2016) - Bani-Hani, Ehab Hussein; Hammad, Mahmoud; Matar, Ali; Sedaghat, Ahmad; Khanafer, Khalil
Highlights: Incineration of polychlorinated biphenyls (PCBs) in a rotary kiln is considered. A stiff nonlinear dynamic model is introduced for solving incineration of PCBs. The model accounts for variations in composition of chlorine atoms and excess air. Results of the proposed incineration model are presented and discussed. Abstract: Polychlorinated biphenyls (PCBs) wastes are among hazardous wastes that must be incinerated for environmental and human health reasons. The incineration process of polychlorinated biphenyls (PCBs) wastes in a rotary kiln are governed by a dynamic model consist of a set of nine stiff nonlinear equations. The dynamic model accounts for variations in composition of PCBs on number of chlorine atoms and process conditions such as excess air, temperature and pressure of operation. To solve these equations, a MATLAB routine is written which is used to study the PCBs waste incineration processes. The results are presented and discussed on the holdups of ash, oxygen, carbon dioxide, water vapor, hydrochloric acid, methane, and gas at different conditions.